Ultrasound mediated release from stimuli-responsive core-shell capsules - Chang, M; Edirisinghe, M; Stride, E (2013)
Delivery systems that facilitate non-invasive, real-time control of drug release have enormous potential in a wide range of therapeutic applications. This study investigates the potential of a new type of core-shell particle for ultrasound-mediated drug delivery. The capsules were prepared using coaxial electrohydrodynamic atomization and consist of a biocompatible polymer (polymethylsilsesquioxane) shell encapsulating a core containing a volatile liquid (perfluorohexane PFH) and a dye (Evans Blue) simulating a drug. The effect of low frequency (20 kHz) ultrasound upon the rate of dye release and capsule surface morphology was investigated for a range of exposure conditions (ultrasound intensity 0.7-26 W cm-2, duty cycle 30-90% and exposure time 0-600 s). The relative proportions of the core liquids were also varied. Incorporation of PFH was found to increase the rate of dye release compared with that from capsules containing dye only. The rate of release was found to be positively correlated with intensity, duty cycle and exposure time; whilst the proportion of PFH did not appear to affect it. Changes in particle surface morphology were only discernible at the higher ultrasound intensities, with pore formation followed by surface cracking and finally shell disintegration being observed with increasing intensity. The presence of the pores was indicative of cavitation activity as was the fact that enhanced release was still observed when the exposure chamber was immersed in an ice bath to minimize heating. It was concluded that the incorporation of PFH into the particles did provide an effective means of producing ultrasound sensitivity which could be exploited in stimuli responsive drug delivery. This journal is © The Royal Society of Chemistry.